Особистісні умови психологічної готовності працівників ОВС до забезпечення громадської безпеки при проведенні масових заходів - Лапчук, В. С.; Lapchuk , V. S. (Вісник Національного університету оборони України. - 2014. - Вип. 1(38). - С. 224-229, 2014)
Стаття присвячена проблемі психологічної готовності працівників міліції до забезпечення громадської безпеки при проведенні масових заходів. Проаналізовано наукові підходи до визначення сутності поняття, різновиди психологічної готовності. Показана структура психологічної готовності. Проаналізовано результати опитування керівного складу ОВС щодо значимості особистісних компонентів у психологічній готовності працівників міліції до забезпечення громадської безпеки при проведенні масових заходів.

The article is devoted to the problem of the psychological readiness of the police to ensure public safety during mass events. There are presented the results of analysis of scientific approaches to defining the essence of the concept of "psychological readiness activities": functional and personality, and types of psychological readiness. The structure of the state of psychological readiness for work is showed. Components of the structure of the individual of police officer, which are likely to affect his state of psychological readiness to ensure public order are obtained from psychogram. The results of the survey managers of police on the importance of the personal component in the formation of the state of psychological readiness of the police to ensure public safety during mass events are presented. There is ascertained, that the basis for the formation of the state of psychological readiness of police officers are professional and psychological preparation.

Статья посвящена проблеме психологической готовности сотрудников милиции к обеспечению общественного порядка при проведении массовых мероприятий. Проанализированы научные подходы к определению сущности понятия, разновидности психологической готовности. Показана структура психологической готовности. Проанализированы результаты опроса руководящего состава ОВД относительно значимости личностных компонентов в состоянии психологической готовности сотрудников милиции к обеспечению общественного порядка при проведении массовых мероприятий.
Personality conditions of psychological readiness policemen to ensure public safety during mass events
Keywords: психологічна готовність; охорона громадського порядку; працівники міліції громадської безпеки; масові заходи; psychological readiness; protection of public order; public security police; public events; психологическая готовность; охрана общественного порядка; сотрудники милиции общественной безопасности; массовые мероприятия